Enhanced sensitization to animal, interpersonal, and intergroup fear-relevant stimuli (but no evidence for selective one-trial fear learning) - Lipp, Ottmar; Cronin, S.; Alhadad, S.; Luck, C. (Blackwell Publishing Inc., 2015)
Selective sensitization has been proposed as an alternative explanation for enhanced responding to animal fear-relevant stimuli—snakes and spiders—during extinction of Pavlovian fear conditioning. The current study sought to replicate the phenomenon using a shock workup procedure as the sensitizing manipulation and to extend it to interpersonal and intergroup fear-relevant stimuli—angry faces and other-race faces. Assessment of selective sensitization was followed by a one-trial fear learning procedure. Selective sensitization, larger electrodermal responses to fear-relevant than to control stimuli after sensitization, or a larger increase in electrodermal responding to fear-relevant than to control stimuli after sensitization was observed across stimulus domains. However, the one-trial fear learning procedure failed to provide evidence for enhanced fear conditioning to fear-relevant stimuli. One-trial fear learning was either absent or present for fear-relevant and nonfear-relevant stimuli. The current study confirms that electrodermal responses to fear-relevant stimuli across stimulus domains are subject to selective sensitization.